Ethical Constraints in Generative Intelligence: Guardrails for Bias Control, Digital Safety, and (Journal of Generative Intelligence E: 3117-6429 P: 3117-6437, 2025)
Generative Intelligence (GI) has rapidly evolved from simple pattern recognition to autonomous multimodal knowledge synthesis. While its applications revolutionize healthcare, finance, defense, law, and governance, its unconstrained deployment introduces ethical vulnerabilities—including bias amplification, identity exploitation, misinformation, autonomous harm, surveillance abuse, and cognitive manipulation. This paper constructs a unified ethical framework that embeds guardrails for bias suppression, safety governance, digital responsibility, algorithmic alignment, and autonomous restraint. It introduces G-SAFE architecture (Generative Safety, Accountability, Fairness, and Ethics)—a multilayer ethical control stack integrating bias auditing, synthetic content watermarking, adversarial containment, autonomy throttling, encrypted model decision tracing, and explainable reasoning paths. Empirical validations show that regulated GI systems trained with ethically bounded reward constraints reduce harmful output generation by 78%, implicit bias propagation by 64%, and hallucination frequency by 51%. The paper concludes by advocating for legally enforceable generative intelligence standards before full-scale autonomous adoption